Deep eutectic solvent-based manganese molybdate nanosheets for sensitive and simultaneous detection of human lethal compounds: comparing the electrochemical performances of M-molybdate (M = Mg, Fe, and Mn) electrocatalysts. Issue 38 (23rd September 2020) - Baby, Jeena N.; Sriram, Balasubramanian; Wang, Sea-Fue; George, Mary; Govindasamy, Mani; Benadict Joseph, Xavier
Abstract : Potentially hazardous chemical contaminants endanger the environment and human well-being, challenging scientists and policy makers to develop holistic alternative approaches for remediation. Abstract : Potentially hazardous chemical contaminants endanger the environment and human well-being, challenging scientists and policy makers to develop holistic alternative approaches for remediation. The addition or accumulation of these chemicals can have a series of far-reaching consequences and have direct and indirect effects at multiple levels of ecological organization. Therefore, the development of a sensitive tool for the comprehensive evaluation of chemical concentrations is highly relevant. Herein, we thus report the simultaneous electrochemical detection of highly toxic hydroquinone (HQ), Hg 2+, and nitrite (NO2 − ) compounds using nanostructured metal molybdate (M = Mg, Fe and Mn) catalysts. These functional nanomaterials are synthesized using a deep eutectic solvent (DES) modified hydrothermal method that provides sustainable aspects and energy efficient synthesis strategies. Choline chloride (ChCl)–urea DES used in this study exhibits an all-in-one behaviour by simultaneously acting as a template, reducing agent, and homogeneous means for stabilizing metal ions. This stimulates the fabrication of hierarchical structures of metal molybdates with high surface activities that cause their remarkable properties with minimal waste generation. The structural, morphological, catalytic, and electrochemical capacities of the as-synthesized MgMoO4, Fe2 (MoO4 )3, and MnMoO4 materials are explored through various techniques and comparatively, MnMoO4 presents superior characterization features such as a reduced particle size, increased surface area and hierarchical architectures. Owing to the exceptional physicochemical attributes, the MnMoO4 modified glassy carbon electrode (GCE) demonstrates superior electrochemical activities towards the individual and simultaneous detection of HQ, Hg 2+, and NO2 − . Well-defined and separate peaks are observed for the simultaneous detection of HQ, Hg 2+, and NO2 − which is influenced by the binding energies of these pollutants. Furthermore, the modified electrode exhibits a high sensitivity of 23.8, 17.7 and 10.2 μA μM −1 cm −2 with a limit of detection (LOD) of 0.026, 0.05, and 0.01 μM for HQ, Hg 2+, and NO2 − respectively under ideal conditions. Also, the reproducibility and anti-interference ability reinforce the application potential of the MnMoO4 modified electrode for the simultaneous electrochemical detection of HQ, Hg 2+, and NO2 − in real samples with better recoveries, thus assessing the effect of these hazardous chemicals on humanity.